CORPORATE CRIMINAL LIABILITY IN ENVIRONMENTAL POLLUTION CRIMES - Setiawan, Deny; Marbun, Warasman; Patramijaya, Arief (JILPR Journal Indonesia Law and Policy Review, 2024)
Environmental law is a set of regulations that regulate the protection and management of the environment. Environmental protection and management is a systematic and integrated effort carried out to preserve environmental functions and prevent environmental pollution and/or damage through structuring, utilization, control, maintenance, supervision and law enforcement.The problems in this journal are:What is the criminal responsibility of corporations as perpetrators of criminal acts of environmental pollution and how?efforts to overcome environmental pollution resulting from criminal acts of environmental pollution committed by corporations.The research method was carried out by methodnormative legal research/normative juridical legal research. This research was conducted to identify the application of corporate criminal responsibility teachings in criminal law enforcement. Based on this research, it can be understood that corporate criminal acts in the environmental sector have widespread and complex negative impacts so that they not only cause direct losses to society and the environment but also disrupt the financial and economic stability of the country, considering that environmental criminal acts are carried out with economic motives. The impact on society includes material losses, health and safety problems, and social and moral losses, namely damage to public trust in business behavior. Administrative environmental law functions to resolve the problem of their actions (environmental pollution), civil environmental law functions to provide legal protection to victims of pollution, and criminal environmental law functions to resolve the problem of polluters (perpetrators of pollution).